ANALISIS NILAI-NILAI RELIGIUS PADA NOVEL TEMAN HEALING KARYA DEDY CHANDRA H - Musyaffa, Bima Surya; wulandari, Ari (Universitas Peradaban, 2024)
Novels are used as a medium for conveying life values. Literary works contain messages and messages in each storyline, so they can be used as lessons in life. The form of messages conveyed can be in the form of human values and religious values that can be used in living life. One of the novels that contains a lot of religious value is the novel Teman Healing by Dedy Chandra H, which was published in December 2022. This book contains motivational sentences that can accompany or serve as teaching for anyone who is in the process of healing or recuperating after a broken heart. . The aim of this research is to describe the religious values contained in the novel Teman Healing by Dedy Chandra H. This research uses descriptive qualitative research. The method used in this research is using library techniques and note taking. In this research the author used the content analysis method (Content Analysis). This novel contains values about Aqidah, namely 1) The value of faith in Allah, 2) The value of faith in Allah's books, 3) The value of faith in Qada and Qadar. Then the Sharia values are 1) The relationship between humans and God, 2) The relationship between humans and humans, 3) The relationship between humans and the universe. And finally, the moral values are 1) Patience, 2) Almsgiving, 3) Sincerity, 4) Stoicism, 5) Tawakal, 6) Endeavor. These values can be used as a guide in living life so that we obtain goodness in this world and in the afterlife.. Keywords: Novel, analysis, religious value.